2015
DOI: 10.1039/c5cc03102h
|View full text |Cite
|
Sign up to set email alerts
|

One-pot tandem catalysis over Pd@MIL-101: boosting the efficiency of nitro compound hydrogenation by coupling with ammonia borane dehydrogenation

Abstract: The hydrogenation efficiency of nitro compounds was found to be greatly boosted by coupling with dehydrogenation of ammonia borane. The Pd@MIL-101 with tiny Pd NPs is exceptionally efficient and recyclable in the tandem reactions and diverse nitro compounds can be selectively reduced to the corresponding amines in 1.5-5 min with quantitative yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(69 citation statements)
references
References 57 publications
0
69
0
Order By: Relevance
“…Their production is heavily dependent on the reduction of their corresponding nitro compounds with noble metal catalysts under high pressures of H 2 and/or high temperatures to boost the contact between H 2 and the nitro compounds . Recently, a tandem catalysis system combining in situ H 2 generation from typical H 2 sources, such as NaBH 4 and NH 3 BH 3 , and reduction of nitro compounds has been proved to be effective to improve the reaction kinetics, because such in situ generated H 2 molecules can react with nitro groups readily . However, noble metal catalysts have the issues of high cost and scarcity, and they often show not well‐matched hydrogen‐generation and nitro‐group‐reduction kinetics in the tandem reactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their production is heavily dependent on the reduction of their corresponding nitro compounds with noble metal catalysts under high pressures of H 2 and/or high temperatures to boost the contact between H 2 and the nitro compounds . Recently, a tandem catalysis system combining in situ H 2 generation from typical H 2 sources, such as NaBH 4 and NH 3 BH 3 , and reduction of nitro compounds has been proved to be effective to improve the reaction kinetics, because such in situ generated H 2 molecules can react with nitro groups readily . However, noble metal catalysts have the issues of high cost and scarcity, and they often show not well‐matched hydrogen‐generation and nitro‐group‐reduction kinetics in the tandem reactions.…”
Section: Methodsmentioning
confidence: 99%
“…[12e,f] Moreover, it has been reported that pyrrolic N species have strong ability to absorb nitro compounds, activate nitro groups, and induce favorable energetic charges during heterogeneous catalytic processes. [16c] For the Co2p XPS data, the signals are relatively weak because most Co species are located inside the silica matrix. The peaks at ≈778.6 and 781.7 eV (Figure D) could be attributed to metallic Co and N‐coordinated Co, respectively, further implying that the N sites can act as coordination and anchoring sites for Co.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is often difficult to realize precise control of the loading position of active NPs relative to the host MOF, because some precursors might deposit on the external surface of MOFs to form aggregated counterparts . To make active NPs exclusively encapsulated inside MOF matrix and prevent them from aggregation, one of the most effective “ship‐in‐a‐bottle” ways by far is the double‐solvent approach, in which metal precursors are introduced into the cavities or channels of MOFs by the capillary force, followed by reduction or heat treatment …”
Section: Controllable Synthesis Of Active Nps Encapsulated By Mofsmentioning
confidence: 99%
“…Cu 2+ @MIL‐101 was prepared via double solvents method according to pervious reports . Typically, activated MIL‐101 (0.200 g) was suspended in 50 ml of dry n ‐hexane as a hydrophobic solvent in a round‐bottomed flask and the mixture was sonicated for 30 min until the sample was dispersed in the n ‐hexane.…”
Section: Methodsmentioning
confidence: 99%